Picture Media as a Solution for Mathematics Learning: A Classroom Action Study on Fourth Grade Elementary School Students - Winarni, Arlisa Tri; Kisyanto, Kisyanto (jurnal matematika, 2025)
Purpose of the study: The aim of this research is to improve mathematics learning outcomes by using image media for angle measurement material for fourth grade elementary school students. Methodology: This classroom action research used observation sheets, essay-type achievement tests, lesson plans, and image-based learning media. The method used followed two cycles of Classroom Action Research (planning, action, observation, and reflection). Data were collected through student achievement tests and then analyzed descriptively using percentage calculations without special software. Main Findings: The use of image-based learning media improved mathematics learning outcomes of fourth-grade students. Classical mastery increased from 25% in the pre-action stage to 50% in Cycle I, showing a 25% improvement. In Cycle II, classical mastery reached 83.3%, indicating a further increase of 33.3% and exceeding the minimum mastery criterion of 75%. Novelty/Originality of this study: This study offers novelty by systematically applying image-based learning media within a classroom action research framework to improve elementary students’ understanding of angle measurement. It provides practical evidence of step-by-step improvement across cycles, enriching empirical knowledge on effective visual media integration in primary mathematics learning.